Radii of harmonic mapping with fixed second coefficients in the plane - AGHALARY, Rasoul; MOHAMMADIAN, Ali (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
In this paper we investigate the radii problem for harmonic functions with a fixed coefficient and determine the radii of univalence, stable starlikness, stable convexity, fully starlikness and fully convexity of order α for these type of functions. All results are sharp. Also these results generalize and improve some results in the literature. Mathematics Subject Classification (2010): 30C45, 30C80.